Determination of Radon Gas Concentration in Fasa Residential Houses and the effects of inhalation on the incidence of lung cancer - javad bahmani; yousef gholampoor (Fasa University of Medical Sciences, 2019)
Background & Objective: The present research project is based on the common ground in nuclear and medicine science. The purpose is to determine the concentration of radon gas in residential homes in Fasa in 1395 for investigating the effects of its inhalation on the incidence of lung cancer in residents of the home. Material & Methods: Among the residential houses, 10 houses were selected in different parts of the city and 20 samples of radon gas infiltration system were installed in these houses in 1395. In this research, using electrochemical stew method, the detectors were scanned by optical scanners and then images of alpha tracks were prepared in the form of image grey scale. After that, with the help of image processing software and using the passive dosimeter method, the mean concentration of radon was determined during a given period of time. Results: The results of counting and measuring the concentration of radon gas in 20 samples collected in two first and second six-month periods of residential buildings were investigated and evaluated. The results showed that radon gas concentrations in Fasa during the first and second six months of 1395 fluctuated from 141 to 417 Becquerel per cubic meter. Conclusion: In both period north-west parts of the Fasa, concentrations above 150 Becquerel per cubic meter was found to be higher than standard concentrations in residential homes, and residents in these areas were at risk of lung cancer. At the end of the article, there are some strategies to reduce the concentration of radon in homes.